Study on the Best Practice of Character Building with Value Clarification Technique Approach at the Integrated Islamic Elementary Schools - Supriatna, Encep (TAWARIKH, 2017)
ABSTRACT: The advancement of time in modern era is not only brough a positive impact but also negative effects, including the degradation of ethics values and politeness. The most effective way to inculcate character building values is through formal education, especially since Elementary School. To anticipate the degradation of ethics values and politeness among children aged 7 to 12 years, there are some SDIT (Sekolah Dasar Islam Terpadu or Integrated Islamic Elementary Schools) try to integrate religious values to anticipate negative impacts of modern life. The purpose of this study is to find out the best practice from some SDITs in Serang City, Banten, Indonesia. Meanwhile, the theory used is VCT (Values Clarification Technique) to dig and to investigate the best values in school as well as its implementation. The method used is survey by giving questionnaires, interviews, and direct observation to the subjects and objects, in this case are SDIT Widya Cendekia, SDIT Al-Izzah, SDIT Peradaban, and SDIT Muhammadiyah in Serang City. The results of this study show that the entire of SDIT have practiced the values and Islamic teachings in daily life of students during school, such as reciting and memorizing short âsurahâ (division of the Al-Qurâan) and daily prayers; help each other; wearing neat clothes; praying âDuhaâ (morning) in congregation; discipline in time; keeping the cleanness of environment; and students have accustomed to give âsadaqahâ (contribution) and âinfaqâ (donation). All the good habits are started from the implementation of character building to students for their future lives. KEY WORDS: Caharacter Building; Ethics Values; Integrated Islamic Elementary Schools; Values Clarification Technique; Best Practice.About the Author: Dr. Encep Supriatna is a Senior Lecturer at the Study Program of Basic Education UPI (Indonesia University of Education) Serang Campus, Jalan Ciracas Lama No.18 Kota Serang, Banten, Indonesia. For academic interests, he can be reached at: cepsup1976@gmail.comRecommended Citation: Supriatna, Encep. (2017). âStudy on the Best Practice of Character Building with Value Clarification Technique Approach at the Integrated Islamic Elementary Schoolsâ in TAWARIKH: International Journal for Historical Studies, Vol.9(1), October, pp.95-114. Bandung, Indonesia: Minda Masagi Press and UIN SGD Bandung, ISSN 2085-0980. Article Timeline: Accepted (March 9, 2017); Revised (July 3, 2017); and Published (October 28, 2017).